Menstrual cycle abnormalities in women vaccinated against COVID-19 - Ioana Zechiu; Nicolae Gica; Radu Botezatu; Gheorghe Peltecu; Anca Maria Panaitescu (Romanian Journal of Infectious Diseases, 2022)
As more reports of menstrual cycle abnormalities after COVID-19 vaccine inoculation are emerging in media and in clinical practice as well, it was deemed necessary to investigate these claims. This review aims to gather current scientific evidence on COVID vaccination’s effect on menstrual cycle. Further and extensive research is undeniably needed to fully understand these phenomena, but current studies have demonstrated an undeniable link between some menstrual cycle abnormalities (especially heavy menstrual flow and variations in cycle length) and breakthrough bleeding in nonmenstruating population and vaccination against SARS-CoV-2. Up to this point, these disturbances seem to be temporary, not lasting for more than a few cycles. The reported menstrual changes have appeared after inoculations of all brands of vaccines, and no particular technology (mRNA or adenovirus-vectored) was particularly associated with them. The greatest concerns raised were those regarding fertility. However, until now, there is no evidence of any of the COVID vaccines affecting fertility when comparing vaccinated and unvaccinated populations.